Resistance to anthelmintics and prevalence of bovine fasciolosis in dairy farms in Jauja, Peru. - Chávez V., Amanda (2012)
The objective of this study was to determine the prevalence of Fasciola hepatica through coprological analysis in dairy cattle in the district of Huertas, province of Junin, Peru and to evaluate the efficacy of two anthelmintics frequently used in the region: triclabendazol (TBCZ) and albendazol (ABZ). Faecal samples were collected from 387 cows in 30 farms. Samples were analysed by the spontaneous sedimentation test and the modified Mc Master test. The prevalence of F. hepatica was 38.2%, with a mean of 16 eggs per gram of faeces (epg) and a range of 1 to 197 epg. Furthermore, 26 farms (86.7%) were positive to F. hepatica. The faecal egg count reduction test (FECRT) was used for evaluating the parasite resistance to the two anthelmintics. For this, 75 animals with more than 12 epg were selected and randomly allocated to two groups: a) TCBZ, 12 mg/kg body weight (n=39) and b) ABZ, 10 mg/kg body weight (n=33). Both drugs were orally administered. The efficacy of TBCZ on days 7, 14, 21, and 28 was 53.4, 53.3, 36.4, and 34.9% respectively, whereas ABZ was zero in all cases. It is concluded that dairy cattle in Huertas, Jauja has a high prevalence of F. hepatica and the parasite shows resistance to albendazol and triclabendazol.